Association between levels of anti-angiogenic isoform of vascular endothelial growth factor A and pulmonary hypertension. (1st November 2016) - Suzuki, Satoshi; Yoshihisa, Akiomi; Yokokawa, Tetsuro; Misaka, Tomofumi; Sakamoto, Nobuo; Sugimoto, Koichi; Yamaki, Takayoshi; Kunii, Hiroyuki; Nakazato, Kazuhiko; Saitoh, Shu-ichi; Takeishi, Yasuchika
Abstract: Backgrounds: Pulmonary hypertension (PH) is characterized by elevated pulmonary arterial pressure due to vasoconstriction and remodeling of the pulmonary microvasculature. Vascular endothelial growth factor (VEGF) is a key contributor for angiogenesis and vasculogenesis. VEGF165b is recently identified as an anti-angiogenic splicing variant of VEGF. The aim of this study was to examine the association between circulating levels of VEGF165b in PH patients under consideration with classifications of PH. Methods and results: We measured plasma levels of VEGF165b in the PH group (pulmonary artery hypertension [PAH], n = 26; chronic thromboembolic pulmonary hypertension [CTEPH], n = 13) and control group (n = 30). Circulating levels of VEGF165b were higher in PH group than controls (97.1 vs. 53.3 pg/ml, P < 0.01). The multiple regression analysis demonstrated that the independent factor to determine the plasma levels of VEGF165b was the presence of PH (P = 0.04). Next, we focused on differences in VEGF165 b levels and classifications of PH. Plasma VEGF165b level was higher only in idiopathic PAH (n = 9) than in control (137.1 vs. 53.3 pg/ml, P < 0.01), but not in PH related to collagen disease (n = 7), congenital heart disease (n = 10) and CTEPH (n = 13). Conclusions: We demonstrated associations between circulating levels of VEGF165 b and classifications of PH. VEGF165b, anti-angiogenic isoform, might contribute to the pathophysiology in PH, especially in idiopathic PAH. The level of plasma VEGF165b might be a novel marker that reflects the pathological conditions in patients with PH.